Gems of wisdom from the Seventh Dalai Lama - translated by Mullin, Glenn H. (New York : Snow Lion Publications, 1999)
The Seventh Dalai Lama (1708-1757) stands as one of the most beloved Buddhist masters in Tibet's long and illustrious history
Keywords: Spiritual life -- Buddhist meditations